Analisis Tingkat Pendapatan Nelayan Dan Lembaga Pemasaran Perikanan Tangkap Di Kabupaten Fakfak Provinsi Papua Barat - Ardha Puspita Sari; Ludia T. Wambrauw; Marcus R. Maspaitella (JFRES Journal of Fiscal and Regional Economy Studies, 2019)
fisheries in Fakfak Regency. This study used a survey method with direct interview techniques for respondents consisting of fishermen, collectors, retailers, wholesalers and processed fisheries traders. The results showed that, the largest income average of capture fisheries marketing institutions in Fakfak district was at large merchant institutions with a level of income of Rp. This is because large traders sell fish in very large quantities with the aim of selling outside the city of Fakfak. A very large cost is proportional to the income received by large traders. However, the lowest income is obtained by retail traders. Fishermen who have higher income from retailers and collectors are also associated with production costs that are not too large when compared to the purchase costs incurred by traders. The average production cost incurred by fishermen is Rp 2,392,272 which consists of fuel costs, storage costs and consumption costs.